Examining the Model of the Curriculum Used by Graphic Design Institutions in Tanzania at Various Levels of Study - Kilonzo, Kiagho Bukheti (Papers in Education and Development, 2018)
This paper examines the model of curricula used by graphic design institutions in Tanzania and proposes more effective means that graphic design institutions could adopt for offering the most appropriate and relevant training in graphic design at certificate, diploma and bachelor ' s degree levels of education. Most big cities in Tanzania are populated with graphic design work with common errors that reflect the designers ' lack of graphic design skills. Most of those designers have received some training in the many computer training centres in these areas due to the huge demand for graphic designers, but they have mostly been trained in some basic computer essentials and information communication technology rather than graphic design per se. Various curricula of different institutions and scholars from different countries are scrutinized in this study. Keywords: Art education, Graphic Design Curriculum, Graphic Design in Tanzania, Model of Curriculum.